DIALECTICAL RELATIONSHIP BETWEEN DEMOCRACY AND LAW IN HO CHI MINH THOUGHT FOR THE RULE OF LAW - Hang, Nguyen Thi Thu (IJRDO- Journal of Educational Research, 2018)
: Democracy and law are seen as progressive values of humanity in the process of development. Democracy is a phenomenon that has emerged from primitive society and exists in the form of communal democracy on the basis of the original communist mode of production. The constitutional and law systems, so called the law, play an important role in defending the freedom of the individual and the fundamental rights in society, provided that the people are sovereign in society. Democracy and law have a dialectical, interrelated and interrelated relationship. Identifying precisely the relationship between these factors is a prerequisite for bringing positive solutions in the process of building and perfecting the rule of law in Vietnam today. This article deals with the basic contents of the relationship between democracy and law in the rule of law in accordance with Ho Chi Minh thought and to assert the important role of each component in the construction of the State. It also contributes to promote social development in general and enhances the process of perfection of the socialist rule-of-law in Vietnam in particular